Hot glide wax treatment and the hardness of the ski running surface - Kuzmin, L.; Tinnsten, M. (The Engineering of sport 7, Volume 2, 2008)
In the cross country skiing community, hot wax treatment of the ski running surface (SRS) is used in order to influence the surface hardness of the skis in relation to the hardness of the snow crystals. This is discussed in a number of scientific papers and recommended in almost every ski waxing manual. The general idea is to decrease (soften) the surface hardness by the use of a soft glide wax treatment for wet snow conditions and to increase (harden) the hardness of the surface by a hard (synthetic) glide wax treatment for cold, dry snow conditions. The question is; does the hot glide wax treatment of the ski running surface influence the surface hardness? And if so, in what way? In our experiment, ski base specimens of UHMWPE (transparent and "graphite") were treated with ski glide wax. Half of the specimens were treated with soft yellow glide wax, and half with hard green glide wax. After the wax treatment, the surface hardness (Shore D) was measured with a durometer. The study revealed that: both soft glide wax and hard glide wax treatment make the SRS softer; after a long immersion (12 hours) in the bath of melted glide wax, both the hardness of the specimens treated with soft glide wax and of those treated with hard glide wax decreased significant. Conclusion: The hot wax treatment of the SRS with available glide waxes cannot make the SRS harder than it was initially (unwaxed).